Current practice of coal discharging operation in Malaysian port - Amin, Amli Mohamed; Ismail, Syuhaida; Arof, Khairul Zahreen Mohd (Journal of Management, Economics, and Industrial Organization, 2019)
Operation delay causes a financial impact to port operation in overall since is a chain process activity. The losses of time during operation was translated to penalty to port operator team. Therefore, this paper comes out with an objective to investigate current practice of coal discharging operation in Malaysian port. This to ensure that any factors led to delay can be detected to avoid subsequent problem especially industrial sectors and Malaysian economics in general. A systematic literature review (SLR) has been conducted to identified the current practice of port from previous research. Data collected from this SLR used in the development of questionnaire. A set of Questionnaire than been distributed to all port handling coal discharge activities in Malaysia. This study managed to collect 82 respondents randomly working in coal discharge team. Based on the SLR and data analysis, this paper found that, focus in coal discharge activities should be on: (1) the good owner, receiving from and delivering good to port; (2) good transmission between ship and coast vice versa; (3) transporting good to port and transmission of good from port; and (4) other criteria. To sum up, the current practice of coal discharging operation in Malaysian port experiencing delay which is not serious yet still affects the cost of operation in overall.
Keywords: Port operation; Coal discharging; Malaysia